Unsuitability of MALDI-TOF MS to discriminate Acinetobacter baumannii clones under routine experimental conditions - Sousa, Clara; Botelho, João; Grosso, Filipa; Silva, Liliana; Lopes, João; Peixe, Luísa (Frontiers in Microbiology, 2015)
MALDI-TOF MS (matrix-assisted laser desorption/ionization time-of-flight mass spectrometry) is now in the forefront for routine bacterial species identification methodologies, being its value for clonality assessment controversial. In this work we evaluated the potential of MALDI-TOF MS for assisting infection control by depicting Acinetobacter baumannii clones. Mass spectra of 58 A. baumannii clinical isolates belonging to the worldwide spread lineages (ST98, ST103, ST208 and ST218) isolated in our country, were obtained and analysed with several chemometric tools (pseudo gel views, peakfind function and partial least squares discriminant analysis). The clonal lineages were obtained using the “Oxford” scheme, belonging ST98, ST208 and ST218 to the international clone II and ST103 to an epidemic clonal lineage (SG5). Additionally, mass spectra of a highly diverse international collection of 38 isolates belonging to 22 STs were obtained for further comparisons. Pseudo gel views and direct peak pattern analysis didn’t allow the discrimination of A. baumannii isolates belonging to ST98, ST103, ST208 or ST218. Moreover, a partial least square discriminant analysis of the mass spectra considering two spectral ranges (2-20kDa and 4-10kDa) revealed a poor degree of discrimination with only 64.6% and 65.8% of correct ST assignments, respectively. Also, mass spectra of the international isolates (n=38, 22STs) revealed a very congruent peak pattern among them as well as among the four lineages included in this work. Despite the increasing interest of MALDI-TOF MS for bacterial typing at different taxonomical levels, we demonstrated, using routine experimental conditions, the unsuitability of this methodology for A. baumannii clonal discrimination.